Integrating technology in ELT at secondary schools in San Salvador de Jujuy - Sivila, Eva Verónica (2014)
Fil: The present research work intends to show how technology enriches and improves the processes of learning and education. Nowadays, teachers and students are exposed to different changes regarding technology; therefore, they have the possibility to obtain more information and be in contact with real contexts and people from other parts of the world, which was not possible years ago. This technology evolution has impacted on the methodology of teaching a foreign language; that is why, foreign language teachers must ponder over the most useful approaches to combine them with technology. As the Author Chapelle points out “the bond between technology and language use in the modern world should prompt all language professionals to reflect on the ways in which technology is changing the profession of English language teaching”. (2003:3) Moreover, the author Doggett states that “technology itself is not inherently good or bad; it is neutral. It is the use of technology that determines whether it is valuable to the learning process”. (2000:2) Technology opens the door to a wide range of materials that help teachers to enhance their students’ skills and self-confidence with the language they are learning. However, technology must be used with responsibility to make the most of it. The contexts in which the present research work has developed its research proves the existence of pros and cons when integrating technology in English Language teaching, especially in English language classes at secondary schools of San Salvador de Jujuy. The data obtained during the investigation provided with certain details that were very useful to understand the benefits and negative outcomes of teaching English through technology as well as the opportunity to analyze and interpret the strategies that teachers use to incorporate technology in the teaching of English as a foreign language at secondary schools.